Helicobacter pylori and its relationship with variations of gut microbiota in asymptomatic children between 6 and 12 years - Benavides-Ward, Araceli (2018)
Objective: To determine the variations in the composition of the intestinal microbiota in asymptomatic children infected with Helicobacter pylori in comparison with children without the infection. Results: Children infected with H. pylori doubled their probability of presenting 3 of 9 genera of bacteria from the gut microbiota, including: Proteobacteria (p = 0.008), Clostridium (p = 0.040), Firmicutes (p = 0.001) and Prevotella (p = 0.006) in comparison to patients without the infection. We performed a nutritional assessment and found that growth stunting was statistically significantly higher in patients infected with H. pylori (p = 0.046).